Accuracy assessment of RTK-GNSS equipped UAV conducted as-built surveys for construction site modelling. Issue 381 (2nd November 2021) - Varbla, Sander; Puust, Raido; Ellmann, Artu
Abstract : Regular as-built surveys have become a necessary input for building information modelling. Such large-scale 3D data capturing can be conducted effectively by combining structure-from-motion and unmanned aerial vehicles (UAV). Using a RTK-GNSS equipped UAV, 22 repeated weekly campaigns were conducted at two altitudes in various conditions. The photogrammetric approach yielded 3D models, which were compared to the terrestrial laser scanning based ground truth. Better than 2.8 cm geometry RMSE was consistently achieved using integrated georeferencing. It is concluded that the RTK-GNSS based georeferencing enables reaching better than 5 cm geometry accuracy by utilising at least one ground control point.